Vibration modal experiments and modal interactions of a large space deployable antenna with carbon fiber material and ring-truss structure. (15th March 2020) - Siriguleng, B.; Zhang, W.; Liu, T.; Liu, Y.Z.
Graphical abstract: Figure 1. The reflector/boom assembly deployed configurations of ring truss satellite is given. Highlights: Experiments of vibration modals are investigated for a large space deployable antenna. Reduced experimental scale model is designed and manufactured. The experimental measurements of the vibration modals are carried out. The natural frequencies and the corresponding modal shapes are obtained. The phenomena of energy transfer are found. Abstract: This paper investigates the vibration modal experiments and the modal interactions for a large space deployable antenna with the ring-truss structure. The reduced scale model of the large deployable ring-truss antenna is firstly introduced briefly. The reduced experimental scale model of the ring-truss structure is designed and is manufactured. The experimental measurements of the vibration modals are carried out for reduced scale model of the ring-truss structure. The natural frequencies and the corresponding modal shapes are obtained for the reduced scale model of the ring-truss structure. The forced vibration experiments of the reduced scale model are also finished for the ring-truss structure. The displacements of the joint point under different excitation frequencies are obtained and are analyzed. A finite element (FE) analysis is finished for the reduced scale model of the ring-truss structure through applying Nastran. The results of the finite element method (FEM) verify the dynamic behaviors of the experimental model. The modal results of the vibration experiments are compared with those of the theoretical analysis and are indicated to be at a good agreement. The phenomena of the energy transfer are observed from the low frequency modal vibration to the high frequency modal vibration in the forced vibration experiments. We also find these phenomena in the process of studying the theoretical model for the ring truss antenna. It is demonstrated that there exist the phenomena of the energy transfer from the low frequency mode vibration to the high frequency mode vibration for the ring truss antenna when the excitation frequency is consistent with the lower order frequency of the vibration.